Um tema em três tempos / A theme in three moments - Miyazaki, Tieko Yamaguchi (Revista de Letras, 2007)
Através da analise do nível da narração de três romances, enquanto resultado do desempenho do sujeito enunciador, o artigo traça uma evolução de um tipo literário brasileiro à proucura de seu próprio discurso. In three novels, through the analyses of the narrative level as a result of the performance of the enunciated subject. The article marks the evolution of a Brazilian litearary type looking for his own form of speech.